비전투 지역 군인의 비만 스트레스, 체중편견 및 건강관리가 체질량지수에 미치는 영향 - 김경진; 나연경 (한국직업건강간호학회지, 2016)
Purpose: The purpose of this study was to identify the obesity stress, weight bias and health care on Body Mass Index (BMI) in soldiers of non-combat area and to provide data for improving the quality of their life. Methods: This research involved 165 soldiers working in non-combat area. Data collection was conducted from November 1 to 20, 2015. Statistical analysis of the collected data were t-test and ANOVA, Scheffé method post hoc analysis, Pearson‘s correlation coefficients, and multiple liner regression using IBM SPSS 22.0. Results: The mean score of obesity stress was moderate (19.05±5.28). The mean score of weight bias was 69.03 and health care was 2.41 points. There are a positive correlation between obesity stress and BMI (r=.19, p<.05). Weight bias (r=-.19, p<.01) and health care (r=-.26, p<.01) among the subjects had negative correlations with BMI. In a multiple liner regression, obesity stress (β=.18, p<.05), health care (β=-.18, p<.05) were associated with BMI. Conclusion: Based on the findings that obesity stress and health care influence BMI, there is a need to control stress and to properly set proper guidelines on health care for soldiers.